Addressing Survey Methodology in the Southern Levant: Applying Different Methods for the Survey of Tel Burna, Israel - Shai, Yitsḥaḳ (Israel exploration journal, 2014)
Surveying in the southern Levant has until recently been limited to basic methods of surface artefact collection. While recent regional studies have begun to integrate other methods, surveys conducted on individual sites — particularly multi-period settlements (tels) — remain outdated. The following study presents the results of two different survey methods applied at the site of Tel Burna, Israel — surface artefact collection and test-pit surveying — and conducts a threeway comparison between the two survey methods and the excavation results, in an effort to promote survey methodology in the region and to determine the best way for surveying such sites. This will help to reduce the expense and damage caused by excavation, while providing further information on the sites, not obtainable through excavation.